Outcome after partial pulpotomy: long-term results of the prospective clinical MMP-9 study - Petrovic, Jelena; Sekundo, Caroline; Gehrig, Holger; Rampf, Sarah; El-Sayed, Shirin; Ritz, Alexander; Mente, Johannes (Oral health & preventive dentistry, 2023)
Purpose: While the objective of partial pulpotomy is to preserve the vitality and function of the pulp tissue, the preoperative pulp status is the main prognostic factor for its success. To date, however, there is little data on long-term success rates. Therefore, the aim of this prospective pilot study was to assess the long-term outcome of partial pulpotomy in permanent teeth after carious pulp exposure without signs or symptoms of irreversible pulpitis, verified clinically, radiographically, and via MMP-9 levels. Materials and Methods: Patients in whom permanent teeth with extremely deep carious lesions were diagnosed as completely asymptomatic (n = 8) or with signs of reversible pulpitis (n = 10) underwent non-selective caries removal followed by a blood test to assess the level of MMP-9. The teeth were thereafter partially pulpotomised, MTA-capped, and immediately restored with composite resin. Follow-up examinations were performed by endodontically experienced examiners focusing on clinical and radiographic assessment. Results: One patient could not be contacted and was lost to follow-up. Overall, the follow-up period ranged from 2-8 years (mean = 4.4 years). The majority of teeth remained functional and without pathology; one tooth was classified as having failed because of a vertical root fracture. There was no statistically significant difference in the groups' success rate (p = 0.3). The estimated overall survival rate was 94.1% (95% CI: 0.84-1.00) after 4 years according to the Kaplan-Meier method. Conclusion: Pulp vitality in permanent teeth can be preserved with high success rates by means of partial pulpotomy after carious pulp exposure in asymptomatic teeth or in teeth with reversible pulpitis.
Gesehen am 06.05.2024